Ramipril versus placebo in kidney transplant patients with proteinuria: a multicentre, double-blind, randomised controlled trial. Issue 4 (April 2016) - Knoll, Greg A; Fergusson, Dean; Chassé, Michaël; Hebert, Paul; Wells, George; Tibbles, Lee Anne; Treleaven, Darin; Holland, David; White, Christine; Muirhead, Norman; Cantarovich, Marcelo; Paquet, Michel; et al.
Summary: Background: Angiotensin-converting enzyme inhibitors have been shown to reduce the risk of end-stage renal disease and death in non-transplant patients with proteinuria. We examined whether ramipril would have a similar beneficial effect on important clinical outcomes in kidney transplant recipients with proteinuria. Methods: In this double-blind, placebo-controlled, randomised trial, conducted at 14 centres in Canada and New Zealand, we enrolled adult renal transplant recipients at least 3-months post-transplant with an estimated glomerular filtration rate (GFR) of 20 mL/min/1·73m 2 or greater and proteinuria 0·2 g per day or greater and randomly assigned them to receive either ramipril (5 mg orally twice daily) or placebo for up to 4 years. Patients completing the final 4-year study visit were invited to participate in a trial extension phase. Treatment was assigned by centrally generated randomisation with permuted variable blocks of 2 and 4, stratified by centre and estimated GFR (above or below 40 mL/min/1·73 m 2 ). The primary outcome was a composite consisting of doubling of serum creatinine, end-stage renal disease, or death in the intention-to-treat population. The principal secondary outcome was the change in measured GFR. We ascertained whether any component of the primary outcome had occurred at each study visit (1 month and 6 months post-randomisation, then every 6 months thereafter). This trial is registered with ISRCTN, number 78129473. Findings: Between Aug 23, 2006, and March 28, 2012, 213 patients were randomised. 109 were allocated to placebo and 104 were allocated to ramipril, of whom 109 patients in the placebo group and 103 patients in the ramipril group were analysed and the trial is now complete. The intention to treat population (placebo n=109, ramipril n=103) was used for the primary analysis and the trial extension phase analysis. The primary outcome occurred in 19 (17%) of 109 patients in the placebo group and 14 (14%) of 103 patients in the ramipril group (hazard ratio [HR] 0·76 [95% CI 0·38–1·51]; absolute risk difference −3·8% [95% CI −13·6 to 6·1]). With extended follow-up (mean 48 months), the primary outcome occurred in 27 patients (25%) in the placebo group and 25 (24%) patients in the ramipril group (HR 0·96 [95% CI 0·55–1·65]); absolute risk difference: −0·5% (95% CI −12·0 to 11·1). There was no significant difference in the rate of measured GFR decline between the two groups (mean difference per 6-month interval: −0·16 mL/min/1·73m 2 (SE 0·24); p=0·49). 14 (14%) of patients died in the ramipril group and 11 (10%) in the placebo group, but the difference between groups was not statistically significant (HR 1·45 [95% CI 0·66 to 3·21]). Adverse events were more common in the ramipril group (39 [38%]) than in the placebo group (24 [22%]; p=0·02). Interpretation: Treatment with ramipril compared with placebo did not lead to a significant reduction in doubling of serum creatinine, end-stage renal disease, or death in kidney transplant recipients with proteinuria. These results do not support the use of angiotensin-converting enzyme inhibitors with the goal of improving clinical outcomes in this population. Funding: Canadian Institutes of Health Research.